Automated approach for the evaluation of glutathione-S-transferase P1-1 inhibition by organometallic anticancer compounds - Sarah A. P. Pereira; A. Catarina Baptista L; Lorenzo Biancalana; Fabio Marchetti; Paul J. Dyson; M. Lúcia M. F. S. Saraiva (Taylor & Francis Group, 2022)
A novel automated method based on sequential injection analysis (SIA), a non-segmented flow injection technique, was developed to evaluate glutathione S-transferase P1-1 (GST P1-1) activity in the presence of organometallic complexes with putative anticancer activity. The assay is based on the reaction of L-glutathione (GSH) and 1-chloro-2,4-dinitrobenzene (CDNB) in the presence of GST P1-1 to afford the GS-DNB conjugate and the reaction may be monitored by an increase in absorbance at 340 nm. A series of ruthenium, iron, osmium and iridium complexes were evaluated as GST P1-1 inhibitors by evaluating their half-maximal inhibitory concentration (IC50). An iridium compound displays the lowest IC50 value of 6.7 ± 0.7 µM and an iron compound displays the highest IC50 value of 275 ± 9 µM. The SIA method is simple to use, robust, reliable, and efficient and uses fewer reagents than batch methods and each analysis takes only 5 minutes.